Lifestyle risk factors for overweight and obesity among rural Indian adults: a community-based prospective cohort study - Rajesh Kumar Rai; Sabri Bromage; Jan-Walter De Neve; Anamitra Barik (Journal of Nutritional Science)
India’s nutrition transition has led to an increased burden of overweight/obesity (body mass index of ≥23 kg/m2), driven by lifestyle factors like poor diet, inactivity, and substance use, prompting public health interventions. However, these interventions lack supporting evidence, especially in rural areas, hindering effective strategies for this population. To address this evidence gap, this study used cohort data (baseline: 2018–19, follow-up: 2022–23) from the Birbhum Population Project (West Bengal, India) to analyse lifestyle risk factors and their association with incidence and remission of overweight/obesity among adults aged ≥18 years (sample: 8,974). Modified Poisson regression model was employed to attain the study objective. From 2017–2018 to 2022–2023, the prevalence of overweight/obesity increased from 15.2% (95% CI: 14.1%–16.4%) to 21.0% (95% CI: 19.7%–22.3%) among men and from 24.1% (95% CI: 22.9%–25.2%) to 33.8% (95% CI: 32.5%–35.1%) among women. Overall, 23.0% (95% CI: 21.8%–24.3%) of adults experienced incidence of overweight/obesity, while 13.9% (95% CI: 12.4%–15.6%) experienced remission. Use of motor vehicles among unemployed participants was associated with incident overweight/obesity (relative risk or RR: 1.058; 95% CI: 1.023–1.095; P: 0.001). Vigorous activity at home (including gardening, yard work, and household chores) was linked to higher odds of recovering from overweight/obesity (RR: 1.065; 95% CI: 1.008–1.125; P: 0.025). Frequent tobacco use (often/daily vs. none) was inversely associated with remission of overweight-obesity (RR: 0.689; 95% CI: 0.484–0.980; P: 0.038), as was each 1 ml in alcohol consumption (RR: 0.995; 95% CI: 0.991–0.999; P: 0.022). Discouraging habitual motor vehicle use may help prevent overweight/obesity, while promoting home-based activities may aid remission, particularly for women who are at higher risk for overweight/obesity.